2002
DOI: 10.1034/j.1399-0004.2002.620609.x
|View full text |Cite
|
Sign up to set email alerts
|

Association between G−308A polymorphism of the tumor necrosis factor‐α gene and 24‐hour ambulatory blood pressure values in type 1 diabetic adolescents

Abstract: Tumor necrosis factor-alpha (TNF-alpha) is an inflammatory cytokine, which also influences blood pressure (BP). The G-308A polymorphism of the TNF-alpha gene is associated with altered TNF-alpha production. The prevalence of the TNF-alpha-308A allele is reportedly higher among patients with type 1 diabetes mellitus (T1DM) than in the healthy population. In this study we investigated whether this genetic polymorphism might correlate with BP values in diabetic adolescents. Ambulatory BP monitoring (ABPM) was per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 18 publications
3
11
0
Order By: Relevance
“…A significant increase in TNF −308 allele A and G/A and A/A genotypes was found in North Indian T1DM cases [17,19]. Similarly, an increase in the prevalence of the TNF −308 A allele was reported in Hungarian diabetic patients [20]. Associations of the TNF/ LTA haplotypes and LTA +249A/G SNP with T1DM, was suggested to be independent of HLA in the Moroccan and Bahraini populations [18,22].…”
Section: Discussionmentioning
confidence: 73%
See 3 more Smart Citations
“…A significant increase in TNF −308 allele A and G/A and A/A genotypes was found in North Indian T1DM cases [17,19]. Similarly, an increase in the prevalence of the TNF −308 A allele was reported in Hungarian diabetic patients [20]. Associations of the TNF/ LTA haplotypes and LTA +249A/G SNP with T1DM, was suggested to be independent of HLA in the Moroccan and Bahraini populations [18,22].…”
Section: Discussionmentioning
confidence: 73%
“…However, several other studies found an independent effect of TNF/LTA with T1DM [17][18][19][20]. TNF involvement in the destruction of pancreatic β-cells [10,11] and multiple inflammatory activities of TNF and LTA cytokines make them plausible targets for revealing molecular susceptibility to T1DM.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In particular, Kriskovszky and colleagues found that the TNF-α 308A was related with the low blood pressure in diabetic adolescents. 31 Another study showed that TNF-α 308G was associated with increased risk of hypertension. 32 Ito et al, 33 investigated the correlation of TNF-α with atherogenic risk factors in women.…”
Section: Tnf-α Gene (-308 G→a and Lt-alpha +252 A→g) As Risk Factors mentioning
confidence: 99%